Comparative Study of Agricultural Wastes Utilization in Cementitious Composites - Marcin Małek; Piotr Smarzewski; Mateusz Jackowski; Waldemar Łasica; Janusz Kluczyński (Journal of Natural Fibers)
The exploration of alternative solutions for natural concrete aggregates is justified in the context of sustainable development and the circular economy. This research seeks to assess the effects on physical, mechanical, and thermal characteristics by incorporating walnut shells (WS), corncobs (CC) and cellulose fibers (CF) as substitutes for fine aggregates in concrete, as opposed to using regular concrete. Various proportions (5%, 10%, and 15% by weight) of each agricultural waste were introduced, resulting in a decrease in concrete density as their ratio increased. Also, the connection between mechanical and thermal properties and the type of agricultural waste used were established for all concrete mixes. In the case of walnut shell, there was an increase in compressive, flexural, and split tensile strength. Furthermore, corncobs showed an increase in most of mechanical properties but only up to 10 wt.% ratio and after that ratio a drop in value was noted. Similar trends to the ones presented in mechanical tests were noted during thermal properties tests. This study also identified correlations between density and compressive strength in concrete incorporating three types of agricultural waste.